Urban land use in Narayanganj: dominance of economic activities, squeezed for social space - Islam, Mohammad Sirajul; Ahmed, Kazi Niaz (The Daily Star, 2014)
The writers are Research Associates of BRAC Institute of Governance and Development, BRAC University.